The use of vignettes for conducting healthcare research - Keane, David; Lang, Alexandra. R.; Craven, Michael P.; Sharples, Sarah (CRC Press, 2012)
Improving healthcare requires engaging with clinicians and patients in order to better understand their needs and expectations. Research methods that are used to conduct healthcare research are selected on the basis of study objectives and practicalities (i.e. finances, resources, time frame, etc.). The methodology of vignettes for conducting healthcare research consists of short descriptive scenarios and/or images to engage participants in hypothetical situations in which their emotional, psychological and sociological responses can be measured. They enable participants to feel comfortable in divulging responses that may be of a sensitive nature and provide insight to situations where they may have little or no experience. Two studies that used vignettes to conduct healthcare research will be discussed in terms of their objectives, conceptualisations, designs and developments, implementations, and outcomes. Validity of the vignettes as a methodology for conducting healthcare research will also be discussed.